Health Effects of Electrolyzed Hydrogen Water for the Metabolic Syndrome and Pre-Metabolic Syndrome: A 3-Month Randomized Controlled Trial and Subsequent Analyses - Reiko Moribe; Marina Minami; Ryoji Hirota; Naw Awn J-P; Shigeru Kabayama; Masamitsu Eitoku; Keiko Yamasaki; Hajime Kuroiwa; Narufumi Suganuma (MDPI AG, 2024)
We studied the effect of three months' use of electrolyzed hydrogen water (EHW, Electrolyzed Hydrogen Water conditioner produced by Nihon Trim Co., Ltd.) on metabolic and pre-metabolic syndrome groups. This research was carried out jointly by Susaki City; Nihon Trim Co., Ltd.; and Kochi University as part of a local revitalization project with health as a keyword. A randomized, placebo-controlled, double-blind, parallel-group trial was conducted to evaluate the clinical impact of EHW on participants who suffered from metabolic syndrome or pre-metabolic syndrome. EHW was produced via electrolysis using a commercially available apparatus (Nihon Trim Co., Ltd., Osaka, Japan). During exercise, oxidative stress increases, and active oxygen species increase. In this study, we examined 181 subjects with metabolic syndrome or pre-metabolic syndrome. Among the group that drank EHW for 3 months, those who also engaged in a high level of physical activity showed a significant difference in waist circumference reduction. Although no significant difference was observed, several positive results were found in the participants who engaged in a high level of physical activity. Urinary 8-OHdG, urinary nitrotyrosine, HbA1c, and blood glucose levels increased in the filtered water (FW) group but decreased in the EHW group. High-sensitivity CRP increased less in the EHW group. 8-Isoprostane decreased more in the EHW group. In subgroup analysis, the EHW group showed a significantly greater reduction in waist circumference than the FW group only when controlled for high physical activity. Based on the result, we suggest that, among participants in the study who suffered from metabolic syndrome and pre-metabolic syndrome in which the level of active oxygen species is said to be higher than in healthy subjects, the group that consumed EHW and also engaged in a high level of physical activity experienced a suppressed or reduced increase in active oxygen species.